A Short Review on Novel Membranes for Gas Separation - Muhammad Mufazzal, Mustaffa; Norazlianie, Sazali (Akademia Baru Publishing (M) Sdn Bhd, 2020)
The area is a membrane that works faster than any publicly accessible scheme. Membrane technology are more useful than other kinds of membranes for CO2/CH4 separation, which includes both carbon and zeolite molecular sieves and amorphous silica matrix. Besides, there are several related to the membrane system such as insufficient heat and chemical stability and plasticisation sensitivity. The further improve the transmitter system's position in the separation of gas and economic saving are the advantage of membrane technology to the world. Despite centuries of studies on the topic, fewer than ten polymer kinds are currently used for business gas separation, and no polymer specifically intended for this function. New membrane must deliver substantial rises in CO2 permeance and selectivity of CO2 / CH4 relative to current technologies to contend internationally.